Cybercampaigns in Latin America: Potentialities and Limitations - Valdez Zepeda, Andrés (2011)
The paper discusses the development of cybercampaigns in America Latina inside the political and democratic transformations during the recent decades, as well as the dawn of socialization using telecommunications and new informational technologies which has been observed in the region. We analyze the case of six countries of the region (Argentina, Brazil, Chile, Colombia, Mexico and Venezuela) that are using telecommunications and the new informational technologies as part of central strategies in political campaigns. It also discussed the potentials and limits of such campaigns. We conclude that cybercampaigns in Latin America are consolidated: their development advances in giant steps. However, this type of campaigns has its limitations for achieve its objectives, due to the low-educated electorate, disappointed in political class.